Immunization With Mycobacterium tuberculosis Antigens Encapsulated in Phosphatidylserine Liposomes Improves Protection Afforded by BCG - Diogo, Gil R.; Hart, Peter; Copland, Alastair; Kim, Mi-Young; Tran, Andy C.; Poerio, Noemi; Singh, Mahavir; Paul, Matthew J.; Fraziano, Maurizio; Reljic, Rajko (Frontiers in Immunology, 2019)
Liposomes have been long considered as a vaccine delivery system but this technology remains to be fully utilised. Here, we describe a novel liposome-based subunit vaccine formulation for tuberculosis (TB) based on phosphatidylserine encapsulating two prominent TB antigens, Ag85B and ESAT-6. We show that the resulting liposomes (Lipo-AE) are stable upon storage and can be readily taken up by both mouse and human antigen presenting cells and that their antigenic cargo is delivered and processed within endosomal cell compartments. The Lipo-AE vaccine formulation combined with the PolyIC adjuvant induced a strong mixed Th1/Th17-Th2 immune response to Ag85B but only a weak response to ESAT-6. An immunisation regimen based on systemic delivery followed by mucosal boost with Lipo-AE resulted in the accumulation of resident memory T cells in the lungs. Most importantly though, when Lipo-AE vaccine candidate was administered to BCG-immunised mice subsequently challenged with low dose aerosol Mycobacterium tuberculosis, we observed a significant reduction of the bacterial load in the lungs and spleen compared to BCG alone. We therefore conclude that the immunization with mycobacterial antigens delivered by phosphatidylserine based liposomes in combination with Poly:IC adjuvant may represent a novel BCG booster vaccination strategy.